Regulation of mRNA Translation by MID1: A Common Mechanism of Expanded CAG Repeat RNAs - Griesche, Nadine; Schilling, Judith; Weber, Stephanie; Rohm, Marlena; Pesch, Verena; Matthes, Frank; Auburger, Georg; Krauss, Sybille (Frontiers in Cellular Neuroscience, 2016)
Expansion of CAG repeats, which code for the disease-causing polyglutamine protein, is a common feature in polyglutamine diseases. RNA-mediated mechanisms that contribute to neuropathology in polyglutamine diseases are important. RNA-toxicity describes a phenomenon by which the mutant CAG repeat RNA recruits RNA-binding proteins, thereby leading to aberrant function. For example the MID1 protein binds to mutant huntingtin (HTT) RNA, which is linked to Huntington’s disease (HD), at its CAG repeat region and induces protein synthesis of mutant protein. But is this mechanism specific to HD or is it a common mechanism in CAG repeat expansion disorders? To answer this question, we have analysed the interaction between MID1 and three other CAG repeat mRNAs, Ataxin2 (ATXN2), Ataxin3 (ATXN3), and Ataxin7 (ATXN7), that all differ in the sequence flanking the CAG repeat. We show that ATXN2, ATXN3 and ATXN7 bind to MID1 in a CAG repeat length-dependent manner. Furthermore, we show that functionally, in line with what we have previously observed for HTT, the binding of MID1 to ATXN2, ATXN3 and ATXN7 mRNA induces protein synthesis in a repeat length-dependent manner. Our data suggest that regulation of protein translation by the MID1 complex is a common mechanism for CAG repeat containing mRNAs.